Photodetectors based on two dimensional materials*Project supported by the National Natural Science Foundation of China (Nos. 61377033, 61574132, 61504136) and the State Key Laboratory of Applied Optics, Changchun Institute of Optics, Fine Mechanics and Physics, Chinese Academy of Sciences. (September 2016) - Lou 娄, Zheng 正; Liang 梁, Zhongzhu 中翥; Shen 沈, Guozhen 国震
Abstract: Two-dimensional (2D) materials with unique properties have received a great deal of attention in recent years. This family of materials has rapidly established themselves as intriguing building blocks for versatile nanoelectronic devices that offer promising potential for use in next generation optoelectronics, such as photodetectors. Furthermore, their optoelectronic performance can be adjusted by varying the number of layers. They have demonstrated excellent light absorption, enabling ultrafast and ultrasensitive detection of light in photodetectors, especially in their single-layer structure. Moreover, due to their atomic thickness, outstanding mechanical flexibility, and large breaking strength, these materials have been of great interest for use in flexible devices and strain engineering. Toward that end, several kinds of photodetectors based on 2D materials have been reported. Here, we present a review of the state-of-the-art in photodetectors based on graphene and other 2D materials, such as the graphene, transition metal dichalcogenides, and so on.